Eosinophilic Granulomatosis With Polyangiitis Presenting With Visual Problems and Subendocardial Fibrosis, A Case Report - Mahshid Talebi‐Taher; Sobhan Mehdipourrabori; Soroush Mostafavi; Mahboubeh Pazoki (Clinical Case Reports)
ABSTRACT This case highlights the atypical presentation of eosinophilic granulomatosis with polyangiitis (EGPA) with neurological and cardiac complications, emphasizing the necessity of early recognition and aggressive treatment to prevent morbidity and mortality.